DIFFERENCES IN MORPHOLOGICAL AREA BETWE EN ATHLETS AND NON-ATLETS IN ELEMENTARY SCHOOLS - Slobodan Stojiljković; Ivan Janković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The goal of this re se arch is to de ter mi ne the dif fe ren ces in morp ho lo gi cal cha racte ri stics of pre-te e na ger spor tsmen and pu pils of the sa me age who are not in vol ved in any sports. The te sted par ti ci pants we re 200 pu pils at the age 13 ± 6 months. The gro up of pupils in vol ved in sports clubs con si sted of 100 pu pils and the gro up of pu pils not in vol ved in sport con si ted of 100 pu pils too. The as ses sment of the morp ho lo gi cal cha rac te ri stics was con duc ted using 12 va ria bles. The stu dent T-test sho wed that the re are sta ti sti cally sig ni fi cant dif fe ren ces bet ween the 2 gro ups of pu pils in fa vo ur of tho se in vol ved in sports clubs which is ex pla i ned by the tran sfor ma ti o nal pro ces of tra i ning.